The Role of Plant-Based Foods in Canadian Diets: A Survey Examining Food Choices, Motivations and Dietary Identity. Issue 4 (4th May 2019) - Clark, Lisa F.; Bogdan, Ana-Maria
ABSTRACT: Used as a replacement for animal-based protein sources, the market for foods containing plant-based proteins (PBPs) continues to grow across North America. As of now, however, few studies of consumer behaviour focus specifically on the dynamics of this development in Canada and so this study looks at how PBPs fit in the current dietary choices of Canadians. Using data collected through a geographically representative nation-wide survey, the analysis shows that past and current consumption of these products are good indicators of future consumption of PBPs. Relatedly, negative stigma attached to earlier versions of PBPs, sometimes referred to as 'fake meat', continues to be an issue with current Canadian consumers. The analysis also demonstrates that personal health and animal/environmental ethics play a significant role in individual decisions to eat PBPs instead of meat. Additionally, issues of availability, affordability and concern over the sensory qualities continue to present barriers to future use.